Exposure to selected pathogens in Geoffroy's cats and domestic carnivores from central Argentina - Uhart, Marcela María (2012)
Wild carnivores share a high percentage of parasites and viruses with closely related domestic carnivores. Because of increased overlap and potential contact with domestic species, we conducted a retrospective serosurvey for 11 common carnivore pathogens in 40 Geoffroy's cats (Leopardus geoffroyi) sampled between 2000 and 2008 within or near two protected areas in central Argentina (Lihué Calel National Park, La Pampa, and Campos del Tuyú National Park, Buenos Aires), as well as five domestic cats and 11 domestic dogs from cattle ranches adjacent to Lihué Calel Park. Geoffroy's cats had detectable antibody to canine distemper virus (CDV), feline calicivirus (FCV), feline coronavirus, feline panleukopenia virus (FPV), Toxoplasma gondii, Leptospira interrogans (serovars Ictero/Icter and Ballum), and Dirofilaria immitis. None of the wild cats had antibodies to feline herpesvirus, feline immunodeficiency virus (FIV), feline leukemia virus, or rabies virus. Domestic dogs had antibodies to CDV, canine adenovirus, canine herpesvirus, and canine parvovirus. Antibodies to FPV, FCV, FIV, and T. gondii were found in domestic cats.We provide the first data on exposure of free-ranging Geoffroy's cats to pathogens at two sites within the core area of the species distribution range, including the first report of antibodies to CDV in this species. We encourage continued monitoring for diseases in wild and domestic carnivores as well as preventive health care for domestic animals, particularly in park buffer zones where overlap is greatest.